Odpowiedzi

2009-12-01T21:35:53+01:00
W(x ) = x³ + ax² +bx -9
Jeżeli pierwiastkami wielomianu są x = -3 i x =1, to wielomianW(x ) =o
W(-3) = (-3)³ +a*(-3)² + b*(-3) -9 =0
W(-3) = -27 + 9a -3b -9 =0
W(-3) = 9a -3b -36 =0

W(1) = 1³ +a*1² +b*1 -9 =0
W(1) = a +b -8 =0

Mamy układ równań:
a +b -8 =0
9a -3b -36 =0 /:3

a +b = 8
3a -b = 12

a = 8 -b
3*(8 - b) - b = 12

a = 8 -b
24 - 3b -b = 12

a = 8 -b
-4b = 12-24

a = 8 -b
-4b = -12 /:(-4)

a =8 -b
b = 3

a = 8-3 =5
b =3


a = 5
b = 3

Odp. Dla a = 5 i b = 3 pierwiastkami wielomianu W(x) są x = -3 i x = 1


3 4 3